Consciousness and Social Behavior of Visitors Tourism as a Culture Cares Environment (Case Study Places in Tulungagung District) - Indrayana, Muhammad Alif; Rusdarti, Rusdarti; Handoyo, Eko (JESS (Journal of Educational Social Studies), 2018)
This study aims to determine the awareness and behavior of tourist visitors as an effort to cultivate the environment, obstacles faced by the tourism office and environmental agencies, as well as efforts made by tourism and environmental agencies for visitors to care about the environment. The type of this research is qualitative research. The research data was collected with several techniques, such as observation, interview, and documentation. Triangulation technique is done by means of triangulation method and source that is by checking the information result of interview with documentation and observation. The result of the discussion about the awareness of the tourist visitors shows that the awareness of the less concerned tourism-related visitors. It proved less tourist visitors know the dangers of waste in the environment. Tourists' social behavior to care less about the environment. This is evident with visitors littering, and no other visitors are rebuking. The obstacles faced by related agencies are human resources problems, eliminating bad thoughts from visitors, and communal waste generated by visitors. Efforts made by the relevant agencies is to create a work program devotion, appeal, and giving a free plastic bag.